Kinematic characteristics based on proficiency in geoduepyeopchagi in taekwondo poomsae koryo - So, J. M.; Kang, S.-S.; Hong, A. R.; Jung, J. M.; Kim, J. J. (Korean Journal of Sport Biomechanics, 2016)
Objective: The purpose of this study was to help improve game performance and provide preliminary data to enhance the efficiency of the kick and stability of the support foot by comparing the kinematic characteristics of the repeated side kick (geodeupyeopchagi) in poomsaeKoryo between expert and non-expert groups. Method: The subjects were divided into 2 groups according to proficiency in Taekwondo, an expert group and a non-expert group (n = 7 in each group), to observe the repeated side-kick technique. Four video cameras were set at a speed of 60 frames/sec and exposure time of 1/500 sec to measure the kinematic factors of the 2 groups. The Kwon3D XPprogramas used to collect and analyze three-dimensional spatial coordinates. Ground reaction force data were obtained through a force plate with a 1.200-Hz frequency. An independent samplesttest was performed, and statistical significance was defined as .05. The SPSS 18.0 software was used to calculate the mean and standard deviation of the kinematic factors and to identify the difference between the experts and non-experts. Results: The angular displacement of the hip joint in both the expert and non-expert groups showed statistical significance on E1 and E4 of the left support foot and E5 of the right foot (p<.05). The angle displacement of the knee joint in both groups showed statistical significance on E4 of the left support foot, and E1 and E2 of the right foot (p<.05). The angular velocity of the lower leg in both groups showed no statistical significance on the left support foot but showed statistical significance on E2 and E6 of the right foot (p<.05). The angular velocity of the foot in both groups showed no statistical significance on the left support foot but showed statistical significance on E2 of the right foot (p<.05). The vertical ground reaction force in both groups showed statistical significance on E2 (p<.05). The center of pressure in all directions in both groups showed statistical significance (p<.5). Conclusion: While performing the repeated side kick (geodeupyeopchagi), the experts maintainedconsistency and stability of the angle of the support leg while the kick foot moved high and fast. On the other hand, the angle of the support foot of non-experts appeared inconsistent, and the kick foot was raised, relying on the support leg, resulting in unstable and inaccurate movement.